CHEMICAL WEATHERING AND CLIMATE - A GLOBAL EXPERIMENT: A REVIEW - Huh Y. (My University, 2003)
How has the Earth maintained a habitable environment while its closest neighbors, Venus and Mars, are currently too hot or too cold? This fortunate state has been attributed to a negative feedback hypothesis that has stood unchallenged for years. In this model, any increase in atmospheric CO2 production is balanced by increased CO2 uptake by silicate weathering under greenhouse conditions. A decrease in atmospheric CO2, then, is balanced by decreased silicate weathering rates under the colder climate. A global experiment utilizing published geochemical data from large rivers at different latitudes helps us test the climate dependence of weathering, central to this hypothesis. When rivers draining granitic shields and basaltic provinces are compared, there is no systematic latitudinal variation (temperature dependence) in the rates of chemical weathering. At global scale the physical mechanisms superimpose a threshold effect on the underlying climate-dependence of silicate weathering. On tropical cratons, the buildup of lateritic regolith suppresses weathering. In the arctic/ subarctic, frost action efficiently removes the regolith and generates physical exposure of silicate rocks to the weathering agents (water, CO2), thereby accelerating reaction. Available field observations do not support the currently standard Clausius-Clapeyron-Arrhenius model.
Keywords: rivers; carbon dioxide; carbon cycle; silicate; Arrhenius